Inhibition and Interaction with Hyaluronidase by Compounds from Hop (Humulus lupulus L) Flowers - Liu1, Ming; Yin2, Hua; Dong2, Jianjun; Xiao1, Lin; Liu1, Ge; Qian2, Zhonghua; Miao3, Jinlai (Asian Journal of Chemistry, 2013)
Hop (Humulus lupulus L.) flowers are widely used in the brewing industry and folk medicine. To study the antiallergic activity of hop flowers, the bioactivity-tailored isolation and detailed chemical characterization were used. The results showed that the active compounds are quercetin, rutin, kaempferol and isorhamnetin, which possessed hyaluronidase inhibitory activity in a concentration-dependent manner in vitro. Fluorescence and circular dichroism spectra were further employed to elucidate the interactions between these four bioactive compounds and hyaluronidase. The results revealed that these compounds could quench the intrinsic fluorescence, reduce the hydrophobicity and induce conformational changes of the hyaluronidase and therefore inhibit the catalytic activity of hyaluronidase. This study suggests that compounds from hop flowers are potential inhibitors of hyaluronidase, indicating a promising strategy for the development of natural antiallergic medicines or functional foods.